2018
DOI: 10.1136/bcr-2017-223663
|View full text |Cite
|
Sign up to set email alerts
|

Gitelman syndrome and primary hyperparathyroidism: a rare association

Abstract: Gitelman syndrome(GS) is a rare autosomal recessive salt-losing tubulopathy of young adults, characterised by hypokalaemia, hypomagnesaemia, hypocalciuria and secondary hyperaldosteronism. Hypercalcaemia due to hypocalciuria in these patients is extremely rare.A 25-year-old healthy woman was referred to the Endocrinology clinic for evaluation of persistent hypokalaemia. She presented with fatigue, myalgias, cramps and paraesthesia. Her physical examination was normal. Laboratory workup revealed: K+ 2.7 mEq/L (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…Bianchetti et al reported the blunted relationship between calcium ions, parathyroid hormone (PTH) and calcitriol in patients with GS 6. Moreover, the typical urinary excretion and blood levels of phosphate indicate normal parathyroid function 1. Some patients with GS may not show hypomagnesaemia or hypocalciuria 3…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bianchetti et al reported the blunted relationship between calcium ions, parathyroid hormone (PTH) and calcitriol in patients with GS 6. Moreover, the typical urinary excretion and blood levels of phosphate indicate normal parathyroid function 1. Some patients with GS may not show hypomagnesaemia or hypocalciuria 3…”
Section: Discussionmentioning
confidence: 99%
“…Gitelman syndrome (GS) is a salt-losing disorder affecting the distal convoluted tubule of the nephron. It is an autosomal recessive disorder with a prevalence of 1/40 000 1. GS represents the clinical manifestations of inactivation of the Slc12a3 genes encoding the thiazide-sensitive sodium chloride cotransporter and the Trpm6-Mg genes encoding the magnesium transporters in the distal convoluted tubule 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, the variant c.602-16G>A and the variant c.2221G>A, both in heterozygosity, were detected in SLC12A3 gene, in a patient with GS and primary hyperparathyroidism. 14 In another study, nine splice site mutations, including c.602-16G>A as a novel splice site mutation, were identified and predicted to lead to a frameshift and premature stopcodon. 15 The variant c.602-16G>A is described on the database of HGMD, as a disease-causing mutation.…”
Section: Discussionmentioning
confidence: 99%
“…15 Furthermore, it is described in dbSNP and ExAC databases, and it's frequency is reported as 0.0016%. 14 The functional analysis of mutations in SLC12A3 gene were performed for a limited number of mutations. Rego et al 14 reported that the variant c.602-16G>A is considered of undetermined significance due to lack of functional analysis confirming the splicing effect.…”
Section: Discussionmentioning
confidence: 99%